Financialisation, indebted workers and labour discipline: Empirical evidence on reduced strike activity in the European Union countries - Barradas, R. (New Political Economy, 2025)
Workers are being denoted by higher resignation and conformism and lesser claimant behaviour due to their lesser engagement in strikes, which indeliberately accepts the significant deterioration of labour conditions, a loss of labour rights and an increase in labour exploitation all over the world in the last five decades. Our argument to explain this puzzling paradox of worsening labour conditions yet less strike activity emphasises that as a result of their more financially fragile position, indebted workers evidence a more self-disciplined attitude and risk-averse behaviour in their workplaces in order to retain their jobs (and income) and honour their financial obligations, which then constrains their claims for higher wages and better labour conditions through engagement in strikes. This study assesses the influence of worker indebtedness on strike activity by performing a panel data econometric analysis from 1995 to 2022 that is focused on European Union countries. Our results confirm that worker indebtedness negatively impacts strike activity in European Union countries, especially in those with the highest levels of worker indebtedness. Our results corroborate that the growth in worker indebtedness is even one of the main drivers behind the decline of strike activity in the European Union countries since the mid-1990s.